Thyroid Diseases Pathogenesis, Diagnosis, and Treatment (Endocrinology, 2018)
This book presents the latest advances in knowledge of the pathogenesis of thyroid diseases and describes the state of the art in their diagnosis and treatment, including newly emerging management approaches. After an opening section that addresses thyroid physiology and laboratory evaluation, each of the major thyroid diseases and their subtypes is discussed, covering goiter and thyroid nodule, thyroiditis, hypothyroidism, hyperthyroidism and thyrotoxicosis, and thyroid carcinoma. Other conditions that affect thyroid function or induce thyroid dysfunction are also considered, e.g., pregnancy, non-thyroidal disorders, and medication use. The book is designed to assist practitioners to achieve optimal outcomes in clinical routine by providing clear guidance on clinical examination, the use of diagnostic tests, first- and second-line therapies, and follow-up. Chapter have been written by recognized experts in the field.